Programa de residência universitária na UFS : avanços e desafios para a permanência a partir da visão dos/as residentes - Plinio, Tatiane Campos Nascimento (2021)
This dissertation had as general objective to analyze the vision of students residing in the São Cristóvão/SE and Aracaju/SE campuses about the University Residency Program (PRU) of the Federal University of Sergipe (UF), as an alternative to assure the stay at the university, in the context of the State's counter-reform. In this sense, the discussion about the contemporary scenario of higher education under the logic of commodification, anchored in neoliberal adjustment, becomes essential to understand the current configuration of student assistance in Brazilian public universities. In the last decade, the demand for student assistance has registered a significant increase, as a result of a set of measures adopted in Lula’s and Dilma’s administrations (2003-2016), especially the higher education expansion policy, which caused a change in the student social-economic profile, through greater participation of the subordinate classes in the access to federal higher education institutions. However, the access to the university banks of this population historically excluded from social goods and services does not guarantee the realization of their right to education, for students manage to complete its graduation, it is also necessary to create conditions that enable the permanence through the provision of their material needs, physical and psychological conditions, among others. The exploratory-descriptive study, with a qualitative and quantitative approach, it was characterized as a documentary and field research, based on historical-dialectical materialism. We used as sources of analysis: management reports, statistical yearbooks, publications on academic performance, books, scientific articles, dissertations, theses, and lives. For data collection, a questionnaire was applied virtual with open and closed questions, through the submission of the instrument called Google Form. The universe was made up of UFS students enrolled in the URP at the São Cristóvão and Aracaju campuses, which at the time of data collection totaled 335 residents, 324 corresponding to the first campus and 11 to the last. The sample was defined based on the per capita family income criterion, with 176 questionnaires sent out. As main results, through the analysis of 76 respondents, we highlight that the URP, although it is a program that partially and unsatisfactorily meets the student demands, in the context of the reduction of social rights of the neoliberal agenda, is a mechanism of educational and social inclusion fundamental to the contribution of the permanence in the UFS of the students from popular classes. It was verified that the URP is operationalized in a precarious way, given the inability to fully meet the demands of food and housing, as well as provide assistance in an expanded manner, such as actions aimed at health, sports and culture. From this perspective, we conclude that institutional efforts need to be made to change this picture, in order to overcome the historical character of student assistance focused, "pocketified" and centralized in housing, income and food programs, recognizing, however, the limits of a comprehensive student assistance, in the context of expansion of higher education and in the framework of bourgeois society.